Secondary reinforcement of portland cement pastes using nanofibers aggregated based on polyvinyl alcohol - Franco Medina, Edgar; Delvasto Arjona, Silvio; Zuluaga Corrales, Héctor Fabio; Amigó Borras, Vicente; Angarita Moncaleano, Irma Inírida (Revista de la Construcción. Journal of Construction, 2013)
This work deals with the behavior of electrospun nanofibers aggregated of poly vinyl alcohol (PVA) as the secondary reinforcement for reducing the drying shrinkage of cement during the curing at early ages; these nanofibers were added as reinforcement to a matrix of ultrafine portland cement paste in two different lengths (6 mm and 12 mm); their behavior was similar to that of polypropylene (PP) fibers embedded in the same matrix. The pastes were characterized by cement laser particle sizer; compression, flexural and impact testing, and failure analysis through scanning electron microscope (SEM). Shrinkage and cracking were measured at early ages. The results showed that the cement pastes with addition of PVA fibers showed improved results compared to cement pastes containing PP fibers. Such composite materials may be useful in making tunnels, grouts for repairing buildings, and in general, in applications that require injection or filling fluid due to characteristics of this type of cement.